2020
DOI: 10.3390/ijms21093291
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of Plasma from Exercised Mice Ameliorates Cognitive Dysfunction by Increasing Hippocampal Neuroplasticity and Mitochondrial Functions in 3xTg-AD Mice

Abstract: Alzheimer’s disease is the most common neurodegenerative brain disease causing dementia. It is characterized by slow onset and gradual worsening of memory and other cognitive functions. Recently, parabiosis and infusion of plasma from young mice have been proposed to have positive effects in aging and Alzheimer’s disease. Therefore, this study examined whether infusion of plasma from exercised mice improved cognitive functions related to the hippocampus in a 3xTg-Alzheimer’s disease (AD) model. We collected pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…Horowitz et al (30) showed that not only was neurogenesis increased in exercising WT mice, but even in inactive aged mice when administered with plasma from the exercised mice. Similar results were reported when 3xTg-AD mice were administered plasma from young, exercised mice (19). This denotes that there is a clear axis between the training-induced systemic changes and the brain.…”
Section: Neurogenesis and Anti-apoptotic Pathwayssupporting
confidence: 87%
See 4 more Smart Citations
“…Horowitz et al (30) showed that not only was neurogenesis increased in exercising WT mice, but even in inactive aged mice when administered with plasma from the exercised mice. Similar results were reported when 3xTg-AD mice were administered plasma from young, exercised mice (19). This denotes that there is a clear axis between the training-induced systemic changes and the brain.…”
Section: Neurogenesis and Anti-apoptotic Pathwayssupporting
confidence: 87%
“…Reflecting on the report, the effect on BDNF could be attributed to a Gpld1-uPA-plasminogen cascade. Finally, these effects were observed as an improved cognitive performance of the mice (19,30).…”
Section: Neurogenesis and Anti-apoptotic Pathwaysmentioning
confidence: 92%
See 3 more Smart Citations